Optimizing Personal Data Protection Legal Framework in Indonesia (a Comparative Law Study) - Lestari, Yuliannova; Mujib, M. Misbahul (UIN Sunan Kalijaga Yogyakarta, 2022)
This study explores the protection of personal data-appealing discourse these days. Globally, 132 countries already have special arrangements to protect personal data. The Bill on the Protection of Personal Data in Indonesia is already in the National Legislation Program. Indonesia does not yet have special regulations regarding protecting personal data. Furthermore, it also discussed personal data protection regulations in several countries, both Europe and Asia. This study uses a comparative study that compares personal data protection among countries for further studies on what matters should be included in the Data Protection Bill for Indonesia. The study showed that personal data protection arrangements certainly differ. Most Data Privacy Protection regulates the same stuff, such as principles, protection mechanisms, rights of data subjects, transfers to third countries, and sanctions. It also showed that the regulation of Personal Data Protection in Indonesia is still not adequately controlled compared to the regulations in other countries